Synthesis and low temperature fluorination of the alkaline-earth palladates Ba2-xSrxPdO3 (x = 0-2) - Baikie, T.; Young, N. A.; Francesconi, M. G. (Progress in Solid State Chemistry, 2007)
Since the discovery of superconductivity in Sr2CuO2F2+δ there has been an increased interest in ternary oxide-fluorides. Sr2CuO2F2+δ is prepared via low temperature (T = 220 °C) reaction routes. Low temperature fluorination induces an interesting structural rearrangement in the parent compound Sr2CuO3, which is a one-dimensional material containing linear chains of vertex sharing CuO4 squares along the crystallographic b axis. Upon fluorination, one oxide is substituted by two fluorides and Cu2+ becomes octahedrally coordinated by four oxides and two fluorides. The fluorinated compound Sr2CuO2F2+δ displays the T-type structure (La2CuO4). Insertion of excess fluorine, δ, also takes place and this fluorine occupies interstitial sites in the T structure. Although the starting material Ca2CuO3 is isostructural to Sr2CuO3, Ca2CuO2F2+δ displays the T′ (Nd2CuO4) structure due to the smaller radius of Ca2+ compared to that of Sr2+. The alkaline-earth palladates with the general formula A2PdO3 (A = Ba, Sr) are isostructural with the A2CuO3 (A = Ca, Sr) materials. We prepared the Ba2-xSrxPdO3 (x = 0-2) series and performed low temperature fluorination, which led to the synthesis of the series Ba2-xSrxPdO2F2+δ (0 ≤ x ≤ 1.5). All the compounds in the Ba2-xSrxPdO2F2+δ series show T′ structure (Ca2CuO2F2+δ). Similarities and differences with Sr2CuO2F2+δ and Ca2CuO2F2+δ will be discussed. © 2007 Elsevier Ltd. All rights reserved.